World Economic Outlook, January 1993. (World Economic Outlook; World Economic Outlook ;, 1992)
This paper highlights that the second part of 1992 has been characterized by flagging consumer and business confidence, weaker-than-expected economic activity-especially in Europe and Japan-and considerable tensions in foreign exchange markets. Despite encouraging signs of increased growth in the United States, these developments have cast new doubts on the prospects for recovery in the industrial world after what has already been two years of weak growth or recession in many countries. The persistent currency turbulence since September 1992 and growing tensions over trade have also contributed to increased uncertainty.